Worksite intervention effects on motivation, physical activity, and health: A cluster randomized controlled trial. (March 2018) - Pedersen, C.; Halvari, H.; Williams, G.C.
Abstract: Objectives: The current study tested the hypothesis that a physical activity (PA) intervention in the worksite would lead to increases in autonomous motivation and perceived competence for PA, self-administered regular PA, and cardiorespiratory fitness (CRF), as well as improvements in health (i.e., reduced blood pressure (BP), waist circumference, and improved cholesterol levels). Moreover, the study tested the self-determination theory (SDT) model of health behaviour change. Design: Cluster randomized controlled trial. Method: Participants from a population of employees working within the area of transport and distribution ( n = 202) were cluster randomized ( n = 6 worksites) to an intervention and a control condition. The 16-week group-based worksite intervention was designed based on the tenets of SDT combined with techniques from motivational interviewing (MI). Participants were assessed at baseline and at post-test five months later. Results: Complete-case analyses applying multivariate and univariate analysis of variance indicated an overall intervention effect, and moderate to small effect sizes (Cohen's d ) in favour of the intervention group on CRF, diastolic BP, and high-density lipoprotein cholesterol (HDL-C), as well as need support for PA, autonomous motivation for PA, and perceived competence for PA. Intention-to-treat analyses demonstrated the same pattern with smaller effect sizes. Path analysis obtained a good fit between the data and the SDT model of health behaviour change. Conclusions: Offering need supportive interventions to enhance autonomous motivation and competence for PA among employees resulted in important improvements in CRF as well as positive changes in health. Trial registration: "My Exercise. A Team-based Workplace Intervention for Increased Exercise", clinicaltrials.gov, NCT02429635, April 14, 2015. Highlights: A worksite physical activity intervention based on self-determination theory (SDT) and motivational interviewing. Moderate increases in cardiorespiratory fitness of clinical relevance. Positive but small changes in diastolic and systolic blood pressure, waist circumference, and non-HDL cholesterol. Co-workers be instructed to behave in a manner that is perceived as supportive of basic psychological needs. Support of the SDT-based model of health behaviour change.